Periodontal Status and Glycaemic Control among Type 2 Diabetic Patients- a Comparable Study between 2 Teaching Hospitals in 2 Geographical Zones in Nigeria - , Modupeoluwa Omotunde Soroye; , Olubunmi Omotunde Onigbinde; , Ibitrokoemi Faye Korubo; , Ayamma Udo Umanah (Archives of Current Research International, 2022)
Background: There is clinical evidence that periodontitis and diabetes mellitus (DM) are interconnected. Thus, periodontitis can promote systemic chronic inflammation that can exacerbate type 2 diabetes mellitus. Methodology: Data was collected with self-administered questionnaire. Glycaemic control and periodontal status were evaluated by glycated Hb values and CPI respectively. Analysis was done using the Statistical Package for Social Sciences version 20.0 (IBM SPSS Statistics Armonk New York). Association of glycaemic index with periodontal status was explored by the χ2 test and statistical significance was set at P < 0.05. Results: One hundred and eighty-five participants with type 2 diabetes were recruited with a female predominance in both centers. Majority of participants were above the fifth decade. The mean duration of diabetes was 8.97±7.14. 73.3% of participants in UPTH and 84.7% in LASUTH were out of (p=0.001). One-fourth of participants in LASUTH and 14.2% of participants from UPTH had poor oral hygiene. Twice participants in LASUTH had good glycaemic control compared to those in UPTH (p=0.001). The periodontal status of majority of the participants in the two centers was between CPI score 2 and 4 (p=0.02). The association between good glycaemic control and gender and between good glycaemic control and age were statistically significant (p=0.014; p=0.001). Conclusion: The periodontal status of participants did not worsen with poor glycaemic control. However, education was significantly associated with extent of control. Periodontal care should be incorporated into the management of the diabetics for improved quality of life.